Is scientific performance a function of funds? - Alona Zharova; Wolfgang Karl Härdle; Stefan Lessmann (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2017)
The management of universities demands data on teaching and research performance. While teaching parameters can be measured via student performance and teacher evaluation programs, the connection of research outputs and their grant antecedents is much harder to check, test and understand. This paper elicits the interdependence structure between third-party expenses (TPE), publications, citations and academic age. To describe the relationship, we analyze individual level data from a sample of professorships from a leading research university and a Scopus database for the period 2001 to 2015. Using estimates from a PVARX model, impulse response functions and a forecast error variance decomposition, we show that analyzing on the high aggregation level of universities does not reflect the behavior of its faculties. We explain the differences in relationship structure between indicators for social sciences and humanities, life sciences and mathematical and natural sciences. For instance, for mathematics and some fields of social sciences and humanities the relationship between the TPE and the number of publications is insignificant, however, the influence of the TPE on the number of citation is significant and positive that indicates the difference between quality and quantity of research outputs. The paper also proposes a visualization of the cooperation between faculties and research interdisciplinarity via the co-authorship structure among publications. We discuss the implications for policy and decision making and suggest recommendations for research management of universities.
Keywords: M10; C32; C55; 330; research performance; decision making; third-party funds; publications; citations; PVARX model